Kunden i centrum - Thorstensson, Amalia (2008)
LRF Konsult is a big consulting-firm with offices located all over Sweden. The corporation offers a wide range of services and a lot of the customers are small businesses active within the green sector. An analysis of the corporation made in 2006 showed that one of LRF Konsults weaknesses is that many customers are unaware of the wide range of services that LRF Konsult offers. The internal communication is believed to play a big role in marketing these services. Therefor, the objective of this thesis has been to investigate why the transfer of customers between accounting consultants and business advisors is not greater and how this can be improved. Theories in communication, motivation and organisation culture have been used in the analysis and empirical data has been collected through qualitative interviews with accounting consultants and business advisors within LRF Konsult.